Wereling - Feasey, Steve (Feiwel and Friends, 2010)
Fourteen-year-old Trey Laporte, having woken up one morning to the discovery that he is a werewolf, finds himself pursued by a psychopathic bloodsucker and in love with an insanely pretty girl who happens to be half vampire.